Mean Free Path of Nuclear Interaction for High-energy Particles in Graphite - Manzano, J. R.; Santochi, O. R.; Anderson, J. C.; Cardoso, J. M. M.; Ghielmetti, H.; Cicchini, A. A. (Naciones Unidas, 1958)
Fil: Manzano, J. R. Comisión Nacional de Energía Atómica; Argentina